CLAVE PARA LOS GÉNEROS DE CLERIDAE DE CHILE (COLEOPTERA) - Solervicens, Jaime (Acta Entomológica Chilena, 2022)
Eigtheen genera of Cleridae (Coleóptera) are recognized for the chilean fauna. The genera Eurymetomorphon, Chilioclerus, Eurymetopum and Silviella, synonymyzed by Kolivác (1997-1998), are maintained as valid taxa. An illustrated key of identification of the genera is provided.